Social Structure as the Root of Improving Criminality in the Era of Pandemic Covid-19 - Sa’diyah, Nur Khalimatus; Enggarsasi, Umi (International Journal of Criminology and Sociology, 2021)
A level in society which is a social structure or patterns that foster community life that has a role in an organization in a group. In the face of the Covid-19 Pandemic, the Middle Class and Lower Class Communities were greatly affected by their social and economic conditions, this has become a problem for the Increase of Crime in the era of the Covid-19 Pandemic. The problems in this study are First, what are the factors causing the social structure as the root of the increase in crime in the Covid-19 pandemic era. Second, how to deal with the increase in crime in the era of the Covid-19 pandemic. The research method used is juridical empirical, using primary and secondary data, and qualitative analysis presented descriptively. The result of this research is that with the existence of a social structure as the cause of crime that occurred during the Pandemic, the government must immediately find a solution and overcome it so that the crime rate can suppress and decrease.